Perencanaan Program Kesehatan Berbasis Analisis Situasi dan Problem Solving Cycle - Dewi Agustina Harahap; Fifi Afifah Hasibuan; Rindi Artika; Zahwa Syaqila; Salsabila Siregar; Rahel Salma Aljeffry; Widya Aliska Hariana; Dhea Puspita; Solehah Aura Ramadhin Br Sianipar; Aspadil Siregar; Lila Mashannum Harahap; Sri Rahmawati Pauji Simangunsong; Diva Taswin (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2026)
Health program planning is an essential process in improving public health status through a systematic and data-driven approach. This study aimed to analyze health program planning based on situational analysis and the problem solving cycle (PSC), as well as to identify the root causes of problems using the fishbone approach. The research employed a descriptive qualitative method supported by simple quantitative data. Data were collected through in-depth interviews, observations, and documentation involving purposively selected informants. The results of the situational analysis identified several major health problems, including stunting, low posyandu attendance, and limited maternal knowledge regarding nutrition. Priority setting using the USG method determined stunting as the main health issue. Furthermore, root cause analysis using a fishbone diagram revealed that stunting was influenced by various factors related to man, machine, method, material, environment, money, and management. The application of the problem solving cycle facilitated systematic intervention planning, including nutrition education, community empowerment, and child growth monitoring. Program implementation demonstrated improvements in maternal knowledge and posyandu attendance. In conclusion, health program planning based on situational analysis, fishbone analysis, and the problem solving cycle proved effective in producing targeted and sustainable interventions.